In silico identification of functional divergence between the multiple groEL gene paralogs in Chlamydiae - FARES, MARIO ALI (My University, 2007)
Background Heat-shock proteins are specialized molecules performing different and essential roles in the cell including protein degradation, folding and trafficking. GroEL is a 60 Kda heat-shock protein ubiquitous in bacteria and has been regarded as an important molecule implicated in chronic inflammatory processes caused by Chlamydiae infections. GroEL in Chlamydiae became duplicated at the origin of the Chlamydiae lineage presenting three distinct molecular chaperones, namely the original protein GroEL1 (Ct110), and its paralogous proteins GroEL2 (Ct604) and GroEL3 (Ct755). These chaperones present differential and independent expressions during the different stages of Chlamydiae infections and have been suggested to present differential physiological and regulatory roles. Results In this comprehensive in silico study we show that GroEL protein paralogs have diverged functionally after the different gene duplication events and that this divergence has occurred mainly between GroEL3 and GroEL1. GroEL2 presents an intermediate functional divergence pattern from GroEL1. Our results point to the different protein-protein interaction patterns between GroEL paralogs and known GroEL protein clients supporting their functional divergence after groEL gene duplication. Analysis of selective constraints identifies periods of adaptive evolution after gene duplication that led to the fixation of amino acid replacements in GroEL protein domains involved in the interaction with GroEL protein clients. Conclusion We demonstrate that GroEL protein copies in Chlamydiae species have diverged functionally after the gene duplication events. We also show that functional divergence has occurred in important functional regions of these GroEL proteins and that very probably have affected the ancestral GroEL regulatory role and protein-protein interaction patterns with GroEL client proteins. Most of the amino acid replacements that have affected interaction with protein clients and that were responsible for the functional divergence between GroEL paralogs were fixed by adaptive evolution after the groEL gene duplication events.
PUBLISHED
Keywords: amino acid; chaperonin; chaperonin 1; chaperonin 2; chaperonin 3; regulator protein; unclassified drug; amino acid; chaperonin; chaperonin 1; chaperonin 2; chaperonin 3; regulator protein; unclassified drug